2022
DOI: 10.3390/ijerph19031692
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Compression with a Pneumatic Cuff on Skeletal Muscles Promotes Muscle Blood Flow and Relieves Muscle Stiffness

Abstract: (1) Purpose: This study aimed to examine whether a pneumatic cuff could promote muscle blood flow and improve muscle stiffness by continuously compressing muscles with air pressure in healthy college students. (2) Method: Twenty-one healthy collegiate students participated in this study. The probe of the near-infrared spectrometer was attached to the upper surface of the left gastrocnemius muscle, and a cuff was wrapped around the left lower leg. The cuff was inflated to 200 mmHg. After 10 min, the cuff was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
(15 reference statements)
1
0
0
Order By: Relevance
“…In line with our hypothesis, Chiu et al [10] validated FSN effectiveness in reducing skeletal muscle hardness around the knee and alleviating knee pain, Nakajima [11,12] demonstrated that increasing blood flow and reducing stiffness in lower limb muscles could relieve knee pain. Building on this, considering the physiological heterogeneity in individual muscles, a self-controlled before-and-after study design with unilateral knee osteoarthritis (KOA) patients was deemed most suitable for our small-sample exploratory pilot trial.…”
Section: Introductionsupporting
confidence: 83%
“…In line with our hypothesis, Chiu et al [10] validated FSN effectiveness in reducing skeletal muscle hardness around the knee and alleviating knee pain, Nakajima [11,12] demonstrated that increasing blood flow and reducing stiffness in lower limb muscles could relieve knee pain. Building on this, considering the physiological heterogeneity in individual muscles, a self-controlled before-and-after study design with unilateral knee osteoarthritis (KOA) patients was deemed most suitable for our small-sample exploratory pilot trial.…”
Section: Introductionsupporting
confidence: 83%